IMF Staff papers : Volume 13 No. 3. (IMF Staff Papers; IMF Staff Papers, 1966)
This paper explores trends in payment imbalances between 1952 and 1964. When desired reserves deviate appreciably from actual holdings, the authorities will sooner or later readjust their economic policies to reduce the magnitude of the deviation. On the assumption that the priorities given in individual countries to domestic and external objectives of economic policy and the attitudes toward the use of various policy instruments remain unchanged, desired reserves would tend to rise chiefly as a result of the increase in the size of expected payments fluctuations. International reserves of all 65 countries of the study rose over the period studied by 2.5 per cent a year. This low rate of increase reflects, however, the large reduction in US reserves. For all countries of the study excluding the United States, the reserves grew by 6.0 per cent a year. Leaving aside the loss of reserves by the United States, reserves of all countries appear, therefore, to have grown roughly in proportion to the value of trade and to the size of payments imbalances.